Karakteristik, Profesionalisme, Skeptisisme Profesional terhadap Persepsi Auditor atas Red Flags - Dhiyaa Zulaika; Novita (JRB-Jurnal Riset Bisnis, 2021)
Purpose of this study was to determine effect of characteristics, professionalism, and professional skepticism on auditor’s perceptions of red flags. The data in this study were obtained through distributing questionnaires, which were filled out by 100 auditors who consistently participated in Continuing Professional Training organized by Indonesian Institute of Public Accountants. This study uses quantitative approach, data analysis using SmartPLS software to measure outer and inner models. The results of this study indicate characteristics had no effect on auditor’s perceptions of red flags, professionalism had effect on auditor’s perceptions of red flags, and professional skepticism had effect on auditor’s perceptions of red flags.